Reviews and Responses for AI-Driven Identification of Contrail Sources: Integrating Satellite Observations and Air Traffic Data - Roosenbrand, Esther; Sun, Junzi; Riggi-Carrolo, Emmanuel; Dubot, Thomas; Sarrat, Claire; Bedouet, Judicaël (Journal of Open Aviation Science, 2024)
See detailed reviews and responses in the PDF file. DOI for the original paper: https://doi.org/10.59490/joas.2023.7209